Application of Edible Film based on Chitosan-PLA in the Prolongation of the Shelf Life of Longan Fruit - Kanani, Nufus; Rahmayetty, Rahmayetty; Wardhono, Endarto Yudho; Wardalia, Wardalia (Chemical Engineering Department, Engineering Faculty, Universitas Sultan Ageng Tirtayasa, 2020)
Longan fruit (Dimacorpus longan lour) is one of non-climacteric tropical fruit. Longan fruit has a short shelf life under room temperature. Pericarp browning and microbial decay are the majir factors reducing the longan shelf life, it can cause the limitation of consuming the longan fruits. An alternative means without toxic and pollution effect for preventing and controlling the the post harvesting fruits are needed such as blend film and edible coating application. Application of edible coating is promising to improve the quality and extend live of post harvested vegetable and fruits. Therefore the aim of this study is to define the potential of Chitosan-PLA (Ch-PLA) composites to extend the shelf life of longan fruits. In this experiment, we investigated those with the effect of PLA content to the chitosan film on water vapour permeability, pH condition, film thickness and weight loss of longan fruits.